Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the equation \(\cos x = -\sin^2 x - 1\) in the interval \([0, 2\pi)\), let's work through the equation step by step.
1. Rewrite the Equation:
[tex]\[ \cos x = -\sin^2 x - 1 \][/tex]
2. Use Pythagorean Identity:
Recall that \(\sin^2 x + \cos^2 x = 1\). Therefore, we can express \(\sin^2 x\) in terms of \(\cos x\):
[tex]\[ \sin^2 x = 1 - \cos^2 x \][/tex]
Substitute \(\sin^2 x\) into the equation:
[tex]\[ \cos x = -(1 - \cos^2 x) - 1 \][/tex]
3. Simplify the Equation:
Simplify the right-hand side:
[tex]\[ \cos x = -1 + \cos^2 x - 1 \][/tex]
[tex]\[ \cos x = \cos^2 x - 2 \][/tex]
4. Rearrange the Equation:
Move all terms to one side to form a quadratic equation:
[tex]\[ \cos^2 x - \cos x - 2 = 0 \][/tex]
5. Solve the Quadratic Equation:
Let \(u = \cos x\). The equation becomes:
[tex]\[ u^2 - u - 2 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula \(u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\), where \(a = 1\), \(b = -1\), and \(c = -2\):
[tex]\[ u = \frac{1 \pm \sqrt{1 + 8}}{2} \][/tex]
[tex]\[ u = \frac{1 \pm 3}{2} \][/tex]
Thus, we have two solutions for \(u\):
[tex]\[ u = 2 \quad \text{and} \quad u = -1 \][/tex]
6. Evaluate the Cosine Values:
- \(\cos x = 2\) is not possible because the cosine function ranges between -1 and 1.
- \(\cos x = -1\) is valid.
7. Determine the Associated \(x\) Value:
If \(\cos x = -1\), the angle \(x\) in the interval \([0, 2\pi)\) is:
[tex]\[ x = \pi \][/tex]
8. State the Final Solution:
The solution to the equation \(\cos x = -\sin^2 x - 1\) in the interval \([0, 2\pi)\) is:
[tex]\[ x = \pi \][/tex]
Expressing the solution in terms of \(\pi\):
[tex]\[ x = \pi \][/tex]
1. Rewrite the Equation:
[tex]\[ \cos x = -\sin^2 x - 1 \][/tex]
2. Use Pythagorean Identity:
Recall that \(\sin^2 x + \cos^2 x = 1\). Therefore, we can express \(\sin^2 x\) in terms of \(\cos x\):
[tex]\[ \sin^2 x = 1 - \cos^2 x \][/tex]
Substitute \(\sin^2 x\) into the equation:
[tex]\[ \cos x = -(1 - \cos^2 x) - 1 \][/tex]
3. Simplify the Equation:
Simplify the right-hand side:
[tex]\[ \cos x = -1 + \cos^2 x - 1 \][/tex]
[tex]\[ \cos x = \cos^2 x - 2 \][/tex]
4. Rearrange the Equation:
Move all terms to one side to form a quadratic equation:
[tex]\[ \cos^2 x - \cos x - 2 = 0 \][/tex]
5. Solve the Quadratic Equation:
Let \(u = \cos x\). The equation becomes:
[tex]\[ u^2 - u - 2 = 0 \][/tex]
Solve this quadratic equation using the quadratic formula \(u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\), where \(a = 1\), \(b = -1\), and \(c = -2\):
[tex]\[ u = \frac{1 \pm \sqrt{1 + 8}}{2} \][/tex]
[tex]\[ u = \frac{1 \pm 3}{2} \][/tex]
Thus, we have two solutions for \(u\):
[tex]\[ u = 2 \quad \text{and} \quad u = -1 \][/tex]
6. Evaluate the Cosine Values:
- \(\cos x = 2\) is not possible because the cosine function ranges between -1 and 1.
- \(\cos x = -1\) is valid.
7. Determine the Associated \(x\) Value:
If \(\cos x = -1\), the angle \(x\) in the interval \([0, 2\pi)\) is:
[tex]\[ x = \pi \][/tex]
8. State the Final Solution:
The solution to the equation \(\cos x = -\sin^2 x - 1\) in the interval \([0, 2\pi)\) is:
[tex]\[ x = \pi \][/tex]
Expressing the solution in terms of \(\pi\):
[tex]\[ x = \pi \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.